Uniformity Jalan Menuju Comparability : (Studi terhadap Standar Akuntansi Keuangan Indonesia) - Rustam Hanafi (AKSES: Jurnal Ekonomi dan Bisnis, 2008)
The accounting information will be more useful when high comparability level. While comparability depends on uniformity. This study investigates whether contents of standard was applied consistence with uniformity consept so that make good decision in accounting. My results indicate that 76,5 % contents of standard was applied consistence with the uniformity concept. The weakness of this study that contents of standard was observed and method was used less comprehensive, therefore this result can’t be generalized.Key words: Rigid, finite, flexibility, comparability and uniformity